Silver-Catalyzed para-Selective C–H Amination of 1-Naphthylamides with Azodicarboxylates at Room Temperature - Li, Quan-Zhe; Wang, Xun-Hui; Hou, Si-Hua; Ma, Yan-Yan; Zhao, Deng-Gao; Zhang, Shu-Yu; Bai, He-Yuan; Ding, Tong-Mei (Synthesis, 2019)
A simple and efficient protocol for para-selective C–H amination of 1-naphthylamide derivatives under silver catalysis is described. This reaction system could proceed without the help of directing group and a broad range of substrates were proved to be well tolerated. In addition, control experiments suggested that this reaction might not proceed via a single-electron-transfer process.
Keywords: transition metal; azodicarboxylates; regioselective; amination